High Efficiency Thermoacoustic Loudspeaker Made with a Silica Aerogel Substrate. Issue 8 (12th July 2018) - La Torraca, Paolo; Bobinger, Marco; Pavan, Paolo; Becherer, Markus; Zhao, Shanyu; Koebel, Matthias; Cattani, Luca; Lugli, Paolo; Larcher, Luca
Abstract: The extremely low thermal effusivity of the silica aerogel is exploited to develop a high efficiency thermoacoustic (TA) loudspeaker with solid substrate. The deposition of the electrically conductive, low heat capacity active film on the silica aerogel surface is achieved with both the spray coating of silver nanowires and the sputter coating of gold films. The uniform spray coating of the hydrophobic silica aerogel is enabled by a low pressure plasma treatment, which however impairs its robustness. The spray‐coated samples prove to be fragile when subjected to elevated temperatures and thus not suitable for TA applications. Sputter coating, not requiring any treatment of the aerogel surface, allows the fabrication of working TA loudspeaker samples with a 100 nm gold active film. The electroacoustic response of the gold‐sputtered silica aerogel TA loudspeaker is characterized at different input power levels. The experimental results are compared with those present in literature, showing an improved efficiency with respect to the other TA loudspeakers with solid substrate. Abstract : Silica aerogel is used to fabricate a high efficiency thermoacoustic loudspeaker. Conductive films are deposited on silica aerogel substrate both via spray coating of silver nanowires and sputtering of nanometric gold layers. The low thermal effusivity of the silica aerogel as substrate enhances the heat injection into the air, improving the transduction efficiency.